A comprehensive study on pyrolysis kinetics of microalgal biomass. (1st January 2017) - Bach, Quang-Vu; Chen, Wei-Hsin
Highlights: Thermal degradation mechanism and pyrolysis kinetics of a microalga are studied. Several kinetic models are tested to fit the experimental pyrolysis data. Increasing the number of reactions improves the model fit quality. The conducted seven-reaction model is recommended for predicting microalga pyrolysis. The devolatilization peak is attributed to degradation of Protein I and Carbohydrate II . Abstract: Pyrolysis of microalgal biomass for biofuels production has attracted much attention. However, detailed degradation mechanism and kinetics of the process have not been fully explored yet. In this study, a non-isothermal pyrolysis of microalga Chlorella vulgaris ESP-31 is thermogravimetrically investigated. Several kinetic models, from a single reaction to seven parallel reactions, are tested to fit the experimental pyrolysis data for finding out the optimal pyrolysis model. The results show that the pyrolysis behavior of the microalga is somewhat different from that of lignocellulosic biomass, stemming from the inherent difference in their compositions. Overall, the kinetic modeling processes show that increasing the number of reactions improves the model fit quality. Curve fitting results indicate that the models consisting of three and less than three reactions are not suitable for microalga pyrolysis. The four-reaction model, via considering the pyrolysis of carbohydrate, protein, lipid and others, can be employed for modeling the thermal degradation; however, it cannot precisely predict the thermal degradation of the shoulder and the small peak. The conducted seven-reaction model further partitions the decomposition processes of carbohydrate and protein into two stages, and explains the thermal degradation well. The model indicates that the devolatilization peak is attributed to the combined degradation of Protein I and Carbohydrate II . The seven-reaction model offers the highest fit quality and is thus recommended for predicting the microalga pyrolysis processes.